1993
DOI: 10.1089/thy.1993.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fractures in Postmenopausal Women with Thyroid Disease

Abstract: We interviewed 300 white postmenopausal women (160 with thyroid disease, 140 without thyroid disease) to investigate whether having thyroid disease or taking thyroid hormone increased the prevalence of having a hip, vertebral, or forearm fracture. Thirty-seven (23%) women with thyroid disease and 45 (32%) women without thyroid disease had had a fracture, and there were no significant differences between these groups in the number or type of fractures. Dose of thyroid hormone and duration of therapy or disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
6

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(68 citation statements)
references
References 15 publications
1
61
0
6
Order By: Relevance
“…Of note, in that study, the risk for hospitalization because of fracture was approximately twofold greater in persons older than 65 years of age with low TSH levels. Another retrospective study (19) found that women with a history of hyperthyroidism or thyroid cancer appeared to have their first fracture earlier than women without thyroid disease, and two recent case-control studies of endogenous hyperthyroidism and fracture had conflicting results (21,48).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in that study, the risk for hospitalization because of fracture was approximately twofold greater in persons older than 65 years of age with low TSH levels. Another retrospective study (19) found that women with a history of hyperthyroidism or thyroid cancer appeared to have their first fracture earlier than women without thyroid disease, and two recent case-control studies of endogenous hyperthyroidism and fracture had conflicting results (21,48).…”
Section: Discussionmentioning
confidence: 99%
“…In a study based upon interviews of 300 white postmenopausal women, no increased fracture risk was found in women taking L-T4 (101). In a study of 1180 patients treated with L-T4, the overall fracture rate in women over 65 years after 5 years was 2.5% in those with low TSH, and 0.9% in those with normal TSH values; the difference was not statistically significant (102).…”
Section: Bone Structure and Metabolismmentioning
confidence: 95%
“…Some reports, including a meta-analysis by Wü ster (9), have suggested that the bone mineral density (BMD) is reduced in patients taking long-term treatment to suppress thyroid stimulating hormone (TSH) (levothyroxine, L-T 4 ) compared with controls (10-13). However, other studies have failed to confirm this decremental effect of L-T 4 treatment on BMD (14)(15)(16)(17) or on the prevalence of fracture (18,19). L-T 4 treatment that does not suppress TSH seems to have little effect on bone (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%